Chemical Evaluation of Shivna Lawhali-Takli (Medium Project) Dam Water Tq.-Kannad, District-Aurangabad, State-Maharashtra India. - Devidas, Shelar Mahendra; Pathrikar, Rashmi Dwarkadas (Asian Journal of Pharmaceutical Research and Development, 2015)
The article gives us detailed information of chemical parameters of Shivna lawhali-takli (medium project) dam water. In this article we are looking forward for such a inherent studies such of chemical parameters of temperature, dissolved oxygen, calcium, sulphate, chloride, ferrous, cobalt, nickel and phosphate. All these chemical parameters were observed in the seasons of winter, summer and monsoon during the year of 2014-2015. Such a results describes that the situation of this dam water in different seasons of months gives natural environmental fluctuation in the chemical parameters.